Correction: DNA vaccination induced protective immunity against SARS CoV-2 infection in hamsterss. - Kit Man Chai; Tsai-Teng Tzeng; Kuan-Yin Shen; Hung-Chun Liao; Jhe-Jhih Lin; Mei-Yu Chen; Guann-Yi Yu; Horng-Yunn Dou; Ching-Len Liao; Hsin-Wei Chen; Shih-Jen Liu (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pntd.0009374.].